2014
DOI: 10.1590/s0080-6234201400002000015
|View full text |Cite
|
Sign up to set email alerts
|

Addressing Practical Issues Related Tto Nursing Care For International Visitors To Hiroshima

Abstract: When nine million foreigners visited Japan in 2013, the federal government set a goal to attract an additional two and a half million visitors including medical tourists by 2020. This research investigates the attitudes and concerns of Japanese nurses when they are in a situation dealing with foreign patients. The data were collected from March through September 2010, from 114 nurses at three hospitals, in close proximity to popular tourist destinations in Hiroshima. A questionnaire was developed for this rese… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
3
2

Relationship

3
2

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 10 publications
(15 reference statements)
1
11
0
Order By: Relevance
“…In this study, the majority of Japanese nurses were most concerned about foreign language communication, informed consent, payment of medication expenses, and lifestyle differences. This result is consistent with that from previous research [8].…”
Section: Discussionsupporting
confidence: 94%
See 3 more Smart Citations
“…In this study, the majority of Japanese nurses were most concerned about foreign language communication, informed consent, payment of medication expenses, and lifestyle differences. This result is consistent with that from previous research [8].…”
Section: Discussionsupporting
confidence: 94%
“…We conducted a cross-sectional study from August 2011 to February 2012. Data were collected from nurses via a questionnaire, hereafter referred to as Mari Meter [8], provided during a rst-level nursing management course conducted by the Japanese Nursing Association for nurses in eight prefectures. We targeted both staff nurses and nurse managers who are involved in providing direct healthcare at their hospitals, which are located in prefectural capitals and popular tourist sites for overseas visitors in Japan.…”
Section: Eligibility Study Design and Proceduresmentioning
confidence: 99%
See 2 more Smart Citations
“…A recent study of nurses in Hiroshima where there are many international visitors describes the dilemma associated with Japanese nurses caring for foreign patients (Nishikawa, Niiya, & Okayasu, ). The investigators found that 82% of inpatient unit nurses had some experience in the care of foreign patients.…”
Section: Introductionmentioning
confidence: 99%